Perancangan Depok Creative Hub Dengan Konsep Arsitektur Kontemporer Di Kota Depok - Mohamad Rizki Dwi Nanda Putra; Harfa Iskandaria; Anggraeni Dyah S. (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
The economic structure of the world economy has shifted from being initially based on natural resources (SDA) to human resources based . This hr-based economic activity is called the creative economy industry. Indonesia as one of the developing countries has a huge amount of natural, cultural, and human resources potential. Every year the creative economy in indonesia contributes quite significantly to the national economy. The Central Bureau of Statistics notes that in 2019 the creative economy on average accounted for 9.8% of the country's GDP of Rp 1,211 trillion. The importance of the creative economy to indonesia is seen from the President's directive that the creative economy should be the backbone of the national economy. The governooor of Wessst Java, Ridwan Kamil, taergeted to build Creative Hub throughout the cities/districts in West Java.In 2020, creative hub development is targeted to be built in seven areas namely Cimahi City, Depok, Sukabumi, Bandung Regency, Garut Regency, Majalengka, and Sumedang. The creative economy is a sector whose potential is limitless, as it is based on human resources. The potential of creative economy continues to be developed, especially in Depok, West Java. So through various considerations and major issues concerning the lack of facilities and infrastructure to develop creative industries sectors. the basis of planning and designing a Creative Hub in Depok. The establishment of this new building combines the concept of Contemporary Architecture. Which is expected to be an iconic building in Depok City. As well as being able to become a new container for Creative Economy actors in Depok city to be able to face the development of the times and welcome the development of creative industries in the future. Keywords: Contemporary Architecture, Creative Economy, Creative Industries